Quadrupole Moment of a Magnetically Confined Mountain on an Accreting Neutron Star in General Relativity - Pedro H. B. Rossetto; Jörg Frauendiener; Andrew Melatos (The Astrophysical Journal)
General relativistic corrections are calculated for the quadrupole moment of a magnetically confined mountain on an accreting neutron star. The hydromagnetic structure of the mountain satisfies the general relativistic Grad–Shafranov equation supplemented by the flux-freezing condition of ideal magnetohydrodynamics, as in previous calculations of the magnetic dipole moment. It is found that the ellipticity, and hence the gravitational wave strain, are up to 12% greater than in the analogous Newtonian system. The direct contribution of the magnetic field to the nonaxisymmetric component of the stress-energy tensor is shown to be negligible in accreting systems such as low-mass X-ray binaries.